2017
DOI: 10.1080/02656736.2017.1366553
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of microwave ablation for the treatment of CRC pulmonary metastases

Abstract: CT-guided percutaneous MWA is a safe and effective minimally invasive method for treating CRC pulmonary metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…61 Among previous investigations, tumor size has remained a fairly consistent limiting factor for the widespread use of ablation, regardless of type of energy used. 52 Prior authors have shown that the most favorable local tumor control has been due to a small tumor size 63 and the creation of 5 mm minimal ablation margin, which is considered a minimum requirement for pulmonary ablation. 48,51,61 In a review by de Baere and colleagues, 48 again, it was shown that poorer outcomes from radiofrequency ablation (RFA) were seen with size greater than 2 cm (HR, 2.10; P ¼ .0027); not surprisingly, similar to findings from other modalities (such as surgery), greater number of metastases (3 nodules, HR, 1.86, P ¼ .011) and shorter DFI were also associated with worse oncologic outcomes.…”
Section: Role Of Transthoracic Ablation For Pulmonary Metastasesmentioning
confidence: 99%
“…61 Among previous investigations, tumor size has remained a fairly consistent limiting factor for the widespread use of ablation, regardless of type of energy used. 52 Prior authors have shown that the most favorable local tumor control has been due to a small tumor size 63 and the creation of 5 mm minimal ablation margin, which is considered a minimum requirement for pulmonary ablation. 48,51,61 In a review by de Baere and colleagues, 48 again, it was shown that poorer outcomes from radiofrequency ablation (RFA) were seen with size greater than 2 cm (HR, 2.10; P ¼ .0027); not surprisingly, similar to findings from other modalities (such as surgery), greater number of metastases (3 nodules, HR, 1.86, P ¼ .011) and shorter DFI were also associated with worse oncologic outcomes.…”
Section: Role Of Transthoracic Ablation For Pulmonary Metastasesmentioning
confidence: 99%
“…A systemic review reported that the incidence rate of pneumothorax after RFA ranged between 1.3% and 60% [11]. Although MWA requires fewer ablation needles and has a lesser ablation duration, the occurrence of pneumothorax after MWA appears to be unchanged, with a reported incidence rate of 21.1-63% [2,12]. In addition, Yoshimatsu et al [13] reported an incidence rate of 10.3% for delayed pneumothorax after RFA.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the outcomes of ablative therapies for lung metastases from CRC [12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31]. RFA was the most frequently used treatment in the listed studies.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…In a study on RFA for lung metastases from various primary tumors, de Baère et al performed subgroup analyses for each group of patients with colon and rectal cancer and reported 5-year OS rates of 56.0% and 49.6% in the colon and rectum groups, respectively [12]. In the other studies, the 3-and 5-year OS rates after ablative therapies for lung metastases from CRC were 44-61% and 20-30%, respectively [21,22,24,26,[28][29][30][31]. Local tumor control rates by ablative therapies were approximately 80-90% in most studies; notably, several studies published from 2018 onward achieved local control rates of 90% or higher [18,19,21,23].…”
Section: Colorectal Cancermentioning
confidence: 99%